KOMUNIKASI INTERPERSONAL BUDDHA DAN IMPLEMENTASI DALAM PELAYANAN KEPADA UMAT - Suryani *; Julia Surya; Partono Nyanasuryanadi; Budi Utomo (Pascasarjana Universitas Hindu Indonesia, 2024)
Human beings, as social creatures, consistently engage in interactions within both their families and organizational or community environments. Communication is a fundamental aspect of these interactions, and ethical communication practices should be carefully observed. Communication involves two individuals and is referred to as interpersonal communication. Throughout his life, Buddha demonstrated numerous examples of how he interacted with his followers. He consistently employed a gentle approach, providing understanding in the face of any issues and responding with compassion. Temples, which serve as places for the Buddhist community to gather, are venues for interactions among fellow Buddhists. This warrants the attention of temple administrators to foster peace and harmony. By implementing the interpersonal communication methods exemplified by Buddha, temple administrators should strive to offer excellent services to the community. This, in turn, can enhance the moral values of the community, allowing individuals to engage in virtuous actions unimpeded. The methods of this article is systematic literature review.